Knowledge Level Overview Nurse about Implementation Documentation Care Nursing at the Karo Health Center, Pematangsiantar City - Maswan; Manurung, Renta (International Journal of Public Health Excellence (IJPHE), 2023)
Happening means health all over remote motherland but saakdeasi be marked with the establishment of the Community Health Center (Puskesmas )” kk partly big nurse Still not enough understand about Standard Care Kepara hatan Republic apply Standard Care Nursing in accordance with standard Indonesian esenel department . So done study on the Knowledge Picture Nurse about implementation documentation nursing at the Karo Health Center, Pematangsiantar City. Researcher, carried out in July -September 2021 with population 10 respondents. Zero fetch done with total sampling technique ie whole respondent made sample. Study This show that Majority have knowledge Enough that is as many people (40%) whereas minority have knowledge Good that is as many as 3 people (30%) and knowledge not enough that is as many as 3 people (30%). Characteristics nurse Karo Health Center, Pematangsiantar City majority have aged 31-40 years that is as many as 5 people (50%), the majority type sex Woman namely 8 people (80%), have HI Diploma education namely as many as 9 people (90%), the majority Work for >10 years that is as many as 6 people (60%). Majority have knowledge Enough that is as many as 5 people (50%). Karo Health Center can know causing problems documentation No complete and optimal so can do programs that can increase quality documentation care nursing so that can increase quality services at the health center.